SIMULATION IN EDUCATIONAL PROCESS - HREHOVÁ, Stella (Trends in education, 2008)
In this contribution are shown the possibilities of simulation creating used in educational process. These simulations are created various ways in Matlab.
Keywords: simulation; animation; Matlab